Parameatal Üretral Kist: Olgu sunumu - (:unkn) unknown (My University, 2017)
On yedi yaşında erkek hasta üretral meatusta 15 mm şişlik ile başvurdu. Değerlendirmede hasta işeme ile ilgili şikayet bildirmedi. Hasta kozmetik amaçlı tedavi arayışındaydı. Genç erkeklerde oldukça nadir görülen parameatal üretral kist benign bir durum olup literatürde olgu sayısı oldukça azdır. Kiste literatür önerisine uygun şekilde tam eksizyon uygulandı. Postoperatif takibinde hastanın hiçbir problemi olmadı

A 17-year-old boy presented with 15 mm swelling on the left side of his urethral meatus. He did not report any voiding symptoms. He was seeking medical treatment due to cosmetic concerns. Parameatal urethral cysts are benign conditions that are rarely reported in the literature. We performed complete excision of the cyst as previously suggested by some authors. On postoperative follow-up, there were no findings of voiding difficulty and cosmetic problem
Reconstructive Urology
Keywords: Tıbbi Araştırmalar Deneysel; Üroloji ve Nefroloji